Penerapan Model Pembelajaran Kooperatif Tipe Talking Chip Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran Matematika Di SMP Negeri 7 Padangsidimpuan - Susi Sulastri Lubis; Mohd.Arifin Lubis; Ida Trisnawati (JURNAL CERMATIKA, 2023)
The research method used is classroom action research using two cycles carried out in the first semester with Number Pattern Material. The sample in this research was 30 students in class VIII-2 of SMP Negeri 7 Padangsidimpuan who would use the Talking Chip Learning Model in learning. The results of the research show that the ability of students' learning outcomes in learning Mathematics through the Talking Chip learning model for class VIII-2 students at SMP Negeri 7 Padangsidimpuan in the Number Patterns material for the 2022/2023 academic year has increased with a completion percentage of 93.3% in the "Good" category. Furthermore, the teacher's ability to manage learning increased to 97.90% with the "Very Good" category. For this reason, the expected results have been fulfilled because they are in accordance with the minimum good category with a percentage of 80%.